Integrating Carmelite Spirituality into Character Education : A Management Model Development - Benediktus Bani; Daniel H. F. Manongga; Yari Dwikurnaningsih (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to develop a management model of character education based on Carmelite spirituality, using the Borg & Gall model with a mixed methods approach. The research subjects were Carmelite School teachers in East Nusa Tenggara. Data were collected using questionnaires, interviews, observations, and document studies. Data analysis used a sequential explanatory approach, in which quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed through thematic coding.  The results of this study: the model of character education management based on CARMEL values, developed using POAC management principles is effective in implementing and becoming a solution to the problems of character education management in Carmelite schools in East Nusa Tenggara, to enhance the quality of educational services. This research strengthens a new perspective on character education management based on religious values. Through religious spirituality, students can foster holistically human values based on their local wisdom. Therefore, a quality management model, based on religious values and integrating local culture, equipped with digital platforms, will improve the effectiveness and quality of education services in schools.